Analysis of Human Resources Career Opportunities in Digital Companies - Indra Rustiawan; Qurnia Fitriyatinur; Heru Sutapa; Eka Kurnia Saputra; Fatimah Malini Lubis (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Human resources (HR) play a central role in helping organizations achieve their goals, particularly in digital companies facing rapid technological and business changes. Alongside advanced infrastructure and technology, companies must establish adaptive policies, including HR empowerment, to ensure workforce potential is utilized effectively and efficiently. This study aims to analyze HR career opportunities in digital companies by examining (1) HR development practices and (2) the transformation of HR career opportunities in the digital era. The study employs a narrative research approach supported by secondary data from books, scholarly journals, and relevant publications. The findings show a clear shift in HR career opportunities from administrative functions toward strategic partner roles in business innovation. HR responsibilities increasingly move beyond payroll and routine administration toward strategic talent management, organizational culture transformation, HR technology integration, and continuous skill development. These results highlight that HR careers in digital companies require stronger strategic, analytical, and technological competencies to align workforce capabilities with organizational competitiveness.